The future of Europe - Scherrer, Peter; Bir, Juliane; Kowalsky, Wolfgang; Kuhlmann, Reinhard; Méaulle, Matthieu (Brussels, 2019)
"This collected volume aims to inform and advance the debate on how to achieve a more social and sustainable Europe. Its four chapters and a conclusion address the nature of Europe, the future of the European Union and the political and economic development of the continent. The book argues that strong and assertive trade unions are the most reliable representatives of working people; however they need to change and evolve in order to be able to combat Europe’s growing populism."